2012
DOI: 10.1371/journal.pone.0032439
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Neutrophil Apoptosis in Quiescent ANCA-Associated Systemic Vasculitis

Abstract: BackgroundANCA-Associated Systemic Vasculitis (AASV) is characterized by leukocytoclasis, accumulation of unscavenged apoptotic and necrotic neutrophils in perivascular tissues. Dysregulation of neutrophil cell death may contribute directly to the pathogenesis of AASV.MethodsNeutrophils from Healthy Blood Donors (HBD), patients with AASV most in complete remission, Polycythemia Vera (PV), Systemic Lupus Erythematosus (SLE), Rheumatoid Arthritis (RA) and renal transplant recipients (TP) were incubated in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 47 publications
(45 reference statements)
5
22
0
Order By: Relevance
“…However, Abdgawad et al . observed that spontaneous apoptosis of neutrophils is decreased in these diseases . Our results also support decreased neutrophil apoptosis in GPA (Supporting information, Fig.…”
Section: Discussionsupporting
confidence: 88%
“…However, Abdgawad et al . observed that spontaneous apoptosis of neutrophils is decreased in these diseases . Our results also support decreased neutrophil apoptosis in GPA (Supporting information, Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Along the same lines, we have recently reported high levels of the cytoplasmic proliferating cell nuclear Ag, thus reflecting a prosurvival state in neutrophils from GPA patients (47). Although in this study no difference was observed in PS externalization in patients with ANCA-associated vasculitis, it has been recently reported that neutrophils from these patients had a delayed apoptosis (48). Regardless of the initiating mechanisms, unscavenged apoptotic neutrophils could release their intracellular content, explaining why patients with ANCA-associated vasculitis develop autoimmunity against neutrophil proteins released in tissues (49).…”
Section: Role Of Macrophages In the Modulation Of Autoimmunity In Gpasupporting
confidence: 57%
“…In addition, in SVV, the prototypical ANCA-related autoimmune disease, elevated levels of granulopoiesis-related transcription factors (eg, CEBP-␤) and cytokines (eg, G-CSF) have been recently implicated in the decreased rate of PMN apoptosis, which suggests a role for the types of PMN death other than apoptosis in the pathogenesis of ANCA-associated autoimmunity. 39 Would the factors involved in the enhanced granulopoiesis of SVV patients also be responsible for skewing PMN death from apoptosis to NETosis, the arousal of pathogenic ANCA may find an explanation. Here we show that NETosis, is both immunogenic and proinflammatory whereas apoptosis is known to be poorly effective in inducing inflammation.…”
Section: Discussionmentioning
confidence: 99%